2013
DOI: 10.3109/10826084.2013.797468
|View full text |Cite
|
Sign up to set email alerts
|

Catch, Treat, and Release: Veteran Treatment Courts Address the Challenges of Returning Home

Abstract: After a decade of war, there is a great need for treatment and alternatives to incarceration for justice-involved veterans. U.S. military service members are returning from combat with substantial mental health challenges, which increase the potential for justice involvement. Veteran Treatment Courts are starting across the nation to meet this need for therapeutic justice. These problem solving courts provide access to treatment and motivation for engagement. Preliminary evidence from a Substance Abuse and Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 19 publications
(20 reference statements)
6
33
0
Order By: Relevance
“…Further, as related to support of others' transformation, we speculate that the fresh start mindset informs consumer responses to programs designed to help vulnerable consumers make a new beginning (e.g., programs that empower at-risk teens to transcend present circumstances and begin anew; programs that support veterans in their transition to a new civilian life; and tax and mortgage programs that enable consumers to leave financial mistakes behind and experience a fresh start) (Livshits, MacGee, and Tertilt 2007;Resnick and Rosenheck 2006;Slattery et al 2013). In four studies, we document that the fresh start mindset (contrasted with the growth mindset) impacts practices related to supporting programs (more and less transformative) for vulnerable others (i.e., disadvantaged youth, at-risk teens, veterans, and tax-burdened adults).…”
mentioning
confidence: 99%
“…Further, as related to support of others' transformation, we speculate that the fresh start mindset informs consumer responses to programs designed to help vulnerable consumers make a new beginning (e.g., programs that empower at-risk teens to transcend present circumstances and begin anew; programs that support veterans in their transition to a new civilian life; and tax and mortgage programs that enable consumers to leave financial mistakes behind and experience a fresh start) (Livshits, MacGee, and Tertilt 2007;Resnick and Rosenheck 2006;Slattery et al 2013). In four studies, we document that the fresh start mindset (contrasted with the growth mindset) impacts practices related to supporting programs (more and less transformative) for vulnerable others (i.e., disadvantaged youth, at-risk teens, veterans, and tax-burdened adults).…”
mentioning
confidence: 99%
“…Prior studies suggest more positive SUD treatment outcomes with close coordination with the legal system (Friedmann et al, 2009;Crane et al, 2014). For example, the VA Veteran's Justice Outreach Program (e.g., coordinates substance use and mental health services and legal issues) shows positive clinical and legal outcomes (Slattery et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Sripada et al (2015) similarly found that general social support was correlatedwith reduced mental health symptoms. Slattery,Dugger, Lamb, and Williams (2013) suggest that one reason for VTC success is the restoration of peers-both in treatment and in the community, particularly peer mentors. Of course, the conclusions of the present study are limited since we lack a control groupand our sample size was small.…”
Section: Discussionmentioning
confidence: 99%